Integrating photon up- and down-conversion to produce efficient light-harvesting materials for enhancing natural photosynthesis. Issue 43 (3rd September 2021) - Jiang, Mingyue; Yuan, Yue; Fang, Yuchen; Liu, Shouxin; Li, Jian; Chen, Zhijun; Pang, Qiuying; Li, Shujun
Abstract : A UCNP@CDs incorporated light-harvesting film, which enables simultaneous conversion of NIR and UV photons in solar light to visible light for enhancing photosynthesis was developed. Abstract : Using light-harvesting materials to enhance natural photosynthesis is attracting much attention in both materials and plant research. The working efficiency of most light-harvesting materials is, however, compromised by a narrow light-harvesting range (either ultraviolet (UV) only, or near-infrared (NIR) only) and a short lifetime of the excited state. We have now developed a new light-harvesting material (UCNP@CDs) from upconverting nanoparticles (UCNPs) and carbon dots (CDs), which has good photon up- and down-converting properties, because of the UCNPs and CDs, respectively. UCNP@CDs efficiently absorbed and converted both UV and NIR light to visible light, with a long lifetime for the excited state. UCNP@CDs was incorporated into a carboxymethylcellulose (CMC) matrix to produce a light-harvesting film that enhances natural photosynthesis, both by isolated chloroplasts and by living plants. Our rationally designed UCNP@CDs/CMC composite light-harvesting film was able to enhance photosynthesis by Arabidopsis thaliana by ∼12%.